2016
DOI: 10.1007/s10802-016-0255-4
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Temperament among Youth with Specific Phobias: Implications for CBT Outcomes

Abstract: Specific phobias (SPs) are characterized by excessive fear or anxiety regarding an object or situation. SPs often result in a host of negative outcomes in childhood and beyond. Children with SPs are broadly assumed to show dispositional over-regulation and fearfulness relative to children without SPs, but there are few attempts to distinguish dispositional patterns among children with SPs. In the present study, we examined trajectories of differing temperamental profiles for youth receiving a CBT-based treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…According to the current findings on the relation from BI and social anxiety disorder to CBT outcomes, there seems to be a need to adjust CBT for youth with high BI and/or social anxiety disorder. Similar conclusions have previously been drawn separately for BI and social anxiety disorders (Capriola et al, 2017;Evans et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…According to the current findings on the relation from BI and social anxiety disorder to CBT outcomes, there seems to be a need to adjust CBT for youth with high BI and/or social anxiety disorder. Similar conclusions have previously been drawn separately for BI and social anxiety disorders (Capriola et al, 2017;Evans et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…It is also possible that the impact of BI diminishes with age (Balle et al, 2022). These results indicate that youth with a history of higher BI benefit from treatment, which has been documented for youth with high BI and specific phobias and preschool children exposed to prevention interventions (Capriola et al, 2017;Ooi et al, 2022).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Theories of temperament suggest that early individual differences in negative affectivity may confer risks for both anxiety and depression in youth (Gulley et al, 2016;Vervoort et al, 2011). Further, previous findings suggest that temperamental characteristics predict children's response to anxiety interventions (e.g., Capriola et al, 2017;Festen et al, 2013;Hirshfeld-Becker, et al, 2010). Specifically, there is evidence that negative affectivity is associated with heightened threat appraisal which can hinder responsiveness to interventions like CBT (Lengua & Long, 2002).…”
Section: Child Temperament and Negative Affectivitymentioning
confidence: 99%
“…In contrast, a number of studies revealed that the onset of specific phobias is in childhood. The average age of specific phobia onset is 8.7 years and depends on the type of phobia, for example, school age children for entomophobia and middle adolescence for scelerophobia ( Capriola et al, 2017 ; Shahriari-Namadi et al, 2018 ; Settineri et al, 2019 ). Furthermore, another study found that around 10% of individuals with specific phobias are preschool children, 7% are boys and 13% are girls ( Paulus et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%